Quantitative characterization of the urine and serum metabolomes of children is essential for ‘omics’ studies - DiBattista, Alicia; Chakraborty, Pranesh (Université d'Ottawa | University of Ottawa, 2018)
Abstract Understanding the long-term health impacts of the early-life exposome requires the characterization and assimilation of multi ‘omics’ data to ultimately link molecular changes to exposures. In this way, markers associated with negative health outcomes, such as increased disease risk, can be ascertained. However, determining the extent and direction of metabolic perturbations relies on comparisons to existing metabolomic reference profiles. While such resources are increasingly available for adult populations, analogous tools for children are decidedly lacking. Lau et al. have compiled robust, translatable quantitative metabolomics data on urine and serum samples for European children across six study locations. Metabolites were associated with body mass index, diet and demographics, and correlated within and between biofluids. As a result, a novel association between urinary 4-deoxyerythronic acid and body mass index was uncovered. This work serves as a crucial reference for future studies in exposomics, and – more broadly – represents a significant step forward for metabolomics by creating the foundation for a comprehensive reference metabolome for children. Please see related article: https://bmcmedicine.biomedcentral.com/articles/10.1186/s12916-018-1190-8